Аналіз трансгенних рослин кукурудзи та соняшнику з підвищеним рівнем стійкості до водного стресу - Комісаренко, А.Г.; Михальська, С.І.; Курчій, В.М.; Сергєєва, Л.Є. (Фактори експериментальної еволюції організмів, 2015)
Aims. The trustworthy selection of transgenic plants essentially makes fast the whole transformation of procedure. The optimization of mass screening of corn and sunflower plants, obtained after Agrobacterium – mediated transformation in planta was created. Methods. Agrobacterium – mediated transformation with pBi2E suppressor of proline dehydrogenase gene was carried out. T0 corn and sunflower plants were tested under stress pressure. Lethal water stress in vitro was simulated by the addition of mannitol. The levels of free proline were measured. Results. The transgenic forms survived under lethal water stress. The free proline levels increased in plant tissues in various manners. The free proline contents maintained the tolerance and viability of transformed plants. Conclusions. The reliable method of the detection of plants, resistant to water stress there were proposed.